The Relationship of Instructional Practices to Student Learning in Rural Schools - John P. Dolly; D. Patricia Katz (Journal of Research in Rural Education, 1986)
This paper describes the results of a study conducted to assess improvement in knowledge, attitudes and behavior of elementary school students in rural schools toward good nutrition. A stratified random sample of ISO elementary teachers was selected from a group of 468 who participated in a summer nutrition education program. Students from the teachers' classrooms served as subjects (n = 3600). Data were collected on the types of instructional activities used by the teachers (traditional vs. nonraditional) and the relationship to students' knowledge, attitudes and behavior. Correlations showed no significant relationship among teacher activity scores and student performance. ANDVA showed teachers who used fewer traditional instructional methods had students with the largest gains.